Assessing performance of container slot allocation heuristics - Marvin Kastner; Malte Peters; Carlos Jahn (Adapting to the Future: Maritime and City Logistics in the Context of Digitalization and Sustainability. Proceedings of the Hamburg International Conference of Logistics (HICL), Vol. 32, 2021)
Purpose: In the last decades, the transport capacities of container vessels have tremendously increased. This leads to longer berth times and greater peak loads at container terminals, especially when schedules are perturbed. Thus, existing container handling processes need to be re-evaluated regarding their adequacy. Methodology: In the first step, the current literature is reviewed: which methods have been used for container slot allocation? In the second step, a simulation study is set up to compare two rule-based heuristics of Güven and Türsel Eliiyi (2014; 2019) with Levelling Stacking and Random Stacking. Findings: It is shown that the two rule-based heuristics of Güven and Türsel Eliiyi lead to shorter berth times than Levelling Stacking or Random Stacking. At the same time, the last two approaches show a clear superiority in workload balancing. The joint storage of container groups at Güven and Türsel Eliiyi leads to congestion at the stacking cranes in both cases for peak loads. Originality: This study is the first to compare these four stacking policies. For generating realistic container flows, data from an existing container terminal have been used. Previously unreported performance indicators are used for comparison. Thus, this study provides new insights for improved rule-based heuristics in future.
urn:nbn:de:gbv:830-882.0162294; hdl:10419/249609; https://econpapers.repec.org/RePEc:zbw:hiclpr:32
Keywords: 650; Port logistics